y+3(y-1)-1=44

Simple and best practice solution for y+3(y-1)-1=44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+3(y-1)-1=44 equation:


Simplifying
y + 3(y + -1) + -1 = 44

Reorder the terms:
y + 3(-1 + y) + -1 = 44
y + (-1 * 3 + y * 3) + -1 = 44
y + (-3 + 3y) + -1 = 44

Reorder the terms:
-3 + -1 + y + 3y = 44

Combine like terms: -3 + -1 = -4
-4 + y + 3y = 44

Combine like terms: y + 3y = 4y
-4 + 4y = 44

Solving
-4 + 4y = 44

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 4y = 44 + 4

Combine like terms: -4 + 4 = 0
0 + 4y = 44 + 4
4y = 44 + 4

Combine like terms: 44 + 4 = 48
4y = 48

Divide each side by '4'.
y = 12

Simplifying
y = 12

See similar equations:

| A=q+qsh | | -6*-6+12/-24= | | sqr(x+12)=x | | 9.02x+3.59(8x-4)=12.03x+0.5612 | | sqr(x+12)=x | | ab+2b=6 | | 3n+(9+3)=15 | | 4(m-6)=7m | | 7c/3=25 | | 495/4000 | | 11x+14z=32 | | 18x+16=18x-16 | | sqr(126-10x)=2x | | 0=24x+6 | | 10+0.75Y=10+0.75y | | 5x-2z=32 | | 11(t-6)+7t=6(3t+5)-8 | | 338=(x)(2x) | | 26n-31n-6n-5n-25n-12=-6 | | ln(3x-1)=ln(x-6) | | 15x-8=12+25 | | 10x-x=40 | | 4[9-(6x-3)]+6x=0 | | y=10sin^2 | | -2x^2+1=17 | | 3+5(5t+1)= | | x^5-7x^4+2x^3-x^2-6x+15=0 | | x-(x*0.05)=25831.29 | | 3x/2-5=10 | | x-(x*0.05)=25460 | | 6x-12=12+2x | | 35-6x= |

Equations solver categories